Unlocking concurrency. - Adl-Tabatabai, Ali-Reza; Kozyrakis, Christos; Saha, Bratin (New York ACM, 2006)
Multicore programming with transactional memory
Keywords: Software; Operating systems; Process management; Multiprocessing/multiprogramming/multitasking.; Concurrency; Theory of computation; Computation by abstract devices; Modes of computation; Parallelism and concurrency; Algorithms; Design